Herbs - natural food preservatives / Nurain Aziman - Aziman, Nurain (2021)
Food preservation is a primary concern of the food industry due to the high demand for better quality. Many food preservation methods have been practiced to prevent deterioration and spoilage of food products, and extend their shelf-life. However, the use of synthetic food preservatives to maintain the quality of food products has become commonplace, therefore consumer concerns about their safety are prompting the food industry to seek out natural alternatives.